Left Radicalism and Religion: Perspectives of New Theoretical and Practical Synthesis - Slobodyanyuk, Anatoliy (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
This article is revision of the Marxist religion theory, and proposed explanation of the «magical renaissance» in actual culture. Argued the integration in the scientific discourse of some concepts borrowed from esoteric discourse, namely the conceptual scheme of «the left / right – way hand». This scheme is able to explain some features of the worldview modes of subjects, which position themselves as «spiritual seekers». The analysis draws conclusions about the possibilities of dialectical updates leftist theory and practice.